Development of Digital Research-Based Learning (D-RBL) strategy in instructional media course - Dian Olifia Talaksoru; Dedi Kuswandi; Saida Ulfa (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
Proper selection and utilization of learning media facilitate information delivery to improve the learning experience. This research develops a Digital Research Based Learning (D-RBL) learning strategy to improve the quality of learning in learning media courses. D-RBL integrates flipped classrooms with research-based learning in a learning syntax consisting of three phases: pre-class, in-class, and post-class. The method used in this research is the research and development (RD) method of the Dick and Carey model, which consists of 10 systematic stages. The validation results showed positive results where the D-RBL strategy was feasible. The results showed that D-RBL effectively improved student learning outcomes and developed interaction, collaboration, and procedural skills. This strategy encourages students to learn and actively take responsibility for their learning, allowing them to apply their knowledge in a real context. D-RBL is considered an innovative step in improving the quality of learning in learning media courses. AbstrakPemilihan dan pemanfaatan media pembelajaran secara tepat memfasilitasi penyampaian informasi sehingga dapat meningkatkan pengalaman belajar. Penelitian ini mengembangkan strategi pembelajaran Digital Research Based Learning (D-RBL) untuk meningkatkan kualitas pembelajaran di mata kuliah media pembelajaran. D-RBL mengintegrasikan flipped classroom dengan pembelajaran berbasis penelitian dalam sebuah sintaks pembelajaran yang terdiri dari tiga fase: pra-kelas, di kelas, dan pasca-kelas. Metode yang digunakan dalam penelitian ini adalah metode penelitian dan pengembangan (RD) model Dick and Carey yang terdiri dari 10 tahapan sistematis. Hasil validasi menunjukkan hasil yang positif dimana strategi D-RBL layak untuk diimplementasikan. Hasil penelitian menunjukkan bahwa D-RBL efektif dalam meningkatkan hasil belajar mahasiswa dan mengembangkan interaksi serta keterampilan kolaborasi, dan prosedural. Strategi ini mendorong mahasiswa didik untuk aktif belajar dan bertanggung jawab atas pembelajarannya sendiri, serta memungkinkan mereka menerapkan pengetahuannya dalam konteks yang nyata. D-RBL dianggap sebagai langkah inovatif dalam meningkatkan kualitas pembelajaran di mata kuliah media pembelajaran.Kata Kunci: digital research-based learning; pembelajaran terbalik; research-based learning; strategi pembelajaran